Computational simulation of flow over stepped spillways - Tabbara, Mazen (2005)
Numerical simulations of water flow over stepped spillways with different step configurations are presented. The finite element computational fluid dynamics module of the ADINA software was used to predict the main characteristics of the flow. This included the determination of the water surface, the development of skimming flow over corner vortices, and the determination of energy dissipation. Since the actual flow is turbulent, the k–ε flow model was used. A two-phase solution process was adopted in order to optimize the overall simulation efficiency. In the first phase, a simple yet reasonable water surface consisting of three straight lines was used as an initial guess and was treated as a fixed wall. In the second phase, the results from the first phase were used as initial conditions and the water surface was treated as a free surface that evolved to attain a steady state configuration. For all the cases considered, the predicted water surface profile over the entire length of the spillway was in close agreement with the experimentally measured water surface profile. The predicted energy dissipation was also comparable to the experimentally attained values.